Distal urethroplasty for fossa navicularis and meatal strictures - Dielubanza, Elodi J. (Transl Androl Urol, 2014)
Distal urethral strictures involving the fossa navicularis and meatus represent a unique subset of urethral strictures that are particularly challenging to reconstructive urologists. Management of distal urethral strictures must take into account not only maintenance of urethral patency but also glans cosmesis. A variety of therapeutic approaches exist for the management of distal urethral strictures, including dilation, meatotomy, extended meatotomy, flap urethroplasty, and substitution grafting. Common etiologies for distal urethral strictures include lichen sclerosus, instrumentation, and prior hypospadias repair. Proper patient selection is paramount to the ultimate success and durability of the treatment, which should be individualized and include an assessment of the stricture etiology, location, and burden, and patient-centered goals of care.